Sustainable clay-based materials stabilised by low-temperature treatments: Salt degradation and chemomechanical approach - Marta Cappai; Giorgio Pia (Results in Engineering, 2025)
Earthen materials represent a low environmental impact alternative, but they are inherently vulnerable to water exposure and degradation processes. For this reason, they often require stabilization through thermal treatments. In this study, temperatures lower than those typically used for ceramic firing were applied, with the aim of preserving the sustainability of the final products. However, while the treated structures exhibit improved water resistance, new degradation mechanisms typical of construction materials, such as salt crystallization, may arise. To investigate this aspect, an experimental campaign has been carried out to assess the resistance to sodium sulfate salt crystallisation. The results have been compared with predictions from a chemomechanical model, which has been adapted in this work through the introduction of a porosity activation factor. The model has been shown to be effective in predicting the onset cycle of degradation, offering a valuable tool for the design of more durable and resilient materials.